2005
DOI: 10.1113/jphysiol.2005.096073
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Enhanced responses of the anterior cingulate cortex neurones to colonic distension in viscerally hypersensitive rats

Abstract: The anterior cingulate cortex (ACC) is critically involved in processing the affective component of pain sensation. Visceral hypersensitivity is a characteristic of irritable bowel syndrome. Electrophysiological activity of the ACC with regard to visceral sensitization has not been characterized. Single ACC neuronal activities in response to colorectal distension (CRD) were recorded in control, sham-treated rats and viscerally hypersensitive (EA) rats (induced by chicken egg albumin injection, I.P). The ACC ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 73 publications
5
85
0
1
Order By: Relevance
“…Although the source of viscerocutaneous afferents likely arises in the MITN, the problem of cutaneous-only and visceral-only responses originate from present findings and those of Gao et al (2006) showing visceral hypersensitization with increased baseline activity and lowered threshold for visceral activation in ACC that were not associated with changes in noxious cutaneous responses. Although it is not known how independent channels process cutaneousonly and visceral-only pain in cingulate cortex, the following possibilities are relevant.…”
Section: Source and Latency Of Visceral Nociceptive Signalmentioning
confidence: 51%
See 1 more Smart Citation
“…Although the source of viscerocutaneous afferents likely arises in the MITN, the problem of cutaneous-only and visceral-only responses originate from present findings and those of Gao et al (2006) showing visceral hypersensitization with increased baseline activity and lowered threshold for visceral activation in ACC that were not associated with changes in noxious cutaneous responses. Although it is not known how independent channels process cutaneousonly and visceral-only pain in cingulate cortex, the following possibilities are relevant.…”
Section: Source and Latency Of Visceral Nociceptive Signalmentioning
confidence: 51%
“…This assures that neuron responses under anesthesia reflect nociceptive activity. There is only one study of ACC neuron responses during colorectal distension (Gao et al, 2006). These neurons were not activated by innocuous distension and only 22% were nociceptive.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not surprising that no consensus has emerged that allows comparison between rat c-fos data and human neuroimaging findings. Other region-specific analysis of neuronal responses to CRD has been carried out using in vivo electrophysiological recording technique [1,22]. Lazovic et al conducted the only reported fMRI study in the rat CRD model [38].…”
Section: Introductionmentioning
confidence: 99%
“…The ACG is a multifunctional region that participates in information processing of visceral sensory data, cognitive control and emotional arousal. [35][36][37][38] It is one of the most commonly activated areas during visceral distension. 39,40 Intriguingly, the nodal centralities in the ACG were found to be positively related to DSS of patients in the current results, which reflected the correlation between information flow through the ACG and symptom severity.…”
Section: Discussionmentioning
confidence: 99%